ANALISIS USAHATANI DAN PEMASARAN KEDELAI DI KECAMATAN KETAPANG KABUPATEN SAMPANG - Ahmad Zubaidi (Universitas Tribhuwana Tunggadewi, 2008)
The aim of this research were to study and analyze the cost, income and profit of soybeans farming, the efficiency and study the pattern of soybeans marketing and marketing margin and price share toward the farmers. The research has been done during May until June, 2004. The research uses simple random sampling population on soybeans farmers. Total respondent were 51 persons. Data used in this analysis were primary and secondary data. Methods analysis used in this study were farming analysis, Revenue Cost Ratio and analysis of margin and price share. The result of the research showed production cost Rp. 2.414.247,64/ha, farming income was Rp. 4.781.047/ha, farming profit was Rp. 2.366.799/ha and R/C value was 1.98. Soybeans’ marketing in Ketapang District consists of two distribution channels, (a) Farmers  Brokers  Collectors, and (b) Farmers  Collectors. The marketing cost of soybeans in commission agent for first channel was Rp. 185/kg, meanwhile the marketing cost of soybeans in buyer-up was Rp. 198/kg for first channel and Rp. 199/kg for second channel. The profit that commission agent received was Rp. 355/kg for first channel, meanwhile profit that buyer-up received that was Rp. 335/kg for first channel and Rp. 901/kg for second channel. The margin value of soybeans marketing in Ketapang District for commission agent was Rp. 575/kg for first channel and in buy-up was Rp. 600/kg for first channel and Rp. 1.163/kg for second channel